Effects of solution pH and processing cycle on nanostructured La2(MoO4)3produced by cyclic microwave radiation - Yanee Keereeta (2018)
La2(MoO4)3with different morphologies were successfully produced by a facile cyclic microwave radiation (CMR) processing of a 2:3 molar ratio lanthanum to molybdenum of La(NO3)3·6H2O and (NH4)6Mo7O24·4H2O in the solutions with different pH values adjusted by 2 M NaOH for different processing cycles. XRD, SEM, TEM, HRTEM and SAED showed that La2(MoO4)3microflowers of nanoflake-like petals could be produced by a 180 W CMR for 15 cycles in the solutions with the pH 7 and 8. The 904 and 887 cm-1Raman symmetric stretching modes as well as the 320 cm-1asymmetric bending modes were detected, and direct energy gaps of the UV-visible spectroscopy were 3.47 and 3.85 eV, respectively. The formation mechanism was also proposed in relation to the experimental results. © 2012 Elsevier B.V. All rights reserved.